THIRD PARTY IN RESTITUTION (COMPENSATION) - Ariyanto, Eko (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
Restitution (Compensation) is a development or can be said to be a shift from criminal fines, this shift does not eliminate the application of criminal fines. The fundamental difference between criminal fines and restitution is that in criminal fines, compensation for losses incurred is given to the state, while in restitution, compensation is given to the victim or their family. In several material laws that regulate restitution, basically only regulate the definition of restitution and the mechanism for submitting applications but do not regulate the definition of third parties who are part of the restitution itself. Therefore, the researcher conducted research through normative methods supplemented by interviews with several law enforcement officials, it is hoped that it will obtain a comprehensive picture of third parties in restitution. The reconstruction carried out by the researcher is found in the Law on Witness and Victim Protection, namely Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Witness and Victim Protection, where the researcher added a formulation regarding third parties who are not criminal perpetrators. The additional article that is a reconstruction of the research is in Article 1 number 12, which reads "A third party is a party other than a criminal perpetrator who has a legal relationship with the perpetrator of a criminal act in the same crime." With the reconstruction of the formulation of the definition of a third party used in several material laws, it is clear and obvious who the legal subjects are who can be qualified to be held accountable for paying restitution.